Penerapan Strategi SQ3R untuk Meningkatkan Keterampilan Membaca Kritis Siswa SMA Negeri 14 Gowa - Jannah, Miftahul; Amelia, Putri; Basri, Muh. Bahly (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
The aim of this research is to find out the effectiveness and influencing factors in implementing the SQ3R strategy to improve the critical reading skills of students at SMA Negeri 14 Gowa. This research uses a descriptive qualitative method, namely research where there are no numbers but the results of the research findings are explained in detail or descriptively. The data collection technique uses interviews, working papers and observation. Data was obtained by analyzing the results written by students on their work papers after reading one of the texts, namely about Poerwadarminta using the SQ3R strategy. Apart from that, the findings data were also obtained from interviews with teachers and students as well as direct observations. The research instruments used interview guides, working papers, and observation guides. The results of the research, based on working papers, interviews and observations, show that the SQ3R strategy has great potential in improving students' critical reading skills. However, to achieve optimal results, it is necessary to implement this strategy continuously and consistently. So, teachers need to provide more intensive guidance, especially for students who still have difficulty identifying information differentially. Apart from that, the stage that contributes most to improving students' critical reading skills in the SQ3R strategy is the recite stage, because at this stage students are required to summarize and restate the information obtained from the reading text without help from reading sources.